Belirli mal vasiyeti - Şentürk, Ekin (My University, 2023)
Çalışmanın konusunu Türk-İsviçre Hukukunda maddi anlamda ölüme bağlı tasarruflardan biri olarak düzenlenmiş bulunan belirli mal vasiyeti kurumu oluşturmaktadır. Bu kapsamda vasiyet kurumunun diğer maddi anlamda ölüme bağlı tasarruflardan ayrılan karakteri ele alınmış, vasiyet tasarrufu yapmakla birlikte mirasbırakanın aslında mirasçıları tasrarufun lehtarı arasında bir borç ilişkisi yarattığına dikkat çekilmiştir.Bu borç ilişkisinin tarafları, tasarrufun lehtarının mirasçılardan farklı olarak cüzi halef sıfatını taşıması özel olarak ele alınmış, bu borç ilişkisi neticesinde doğan vasiyet alacağının ifası ve ifa edilmemesine özel olarak değinilmiştir.

The subject of this study is the specific bequest or legacy, which is regulated as one of the testamentary dispositions in the Turkish-Swiss Law. In this context, the character of the testamentary disposition, which differs from other testamentary dispositions in the material sense, is discussed, and it is pointed out that the testator actually creates a debt relationship between the heirs and the beneficiary of this testamentary disposition, legatee. The parties of this debt relationship, the fact that the beneficiary of the disposition bears the title of minor successor unlike the heirs are specifically discussed, and the performance and non-performance of the testamentary receivable arising from this debt relationship are specifically addressed.
Keywords: Aile hukuku; Belirli Mal Vasiyeti; Civil law; Domestic relations; Execution of the Will; Inheritance and succession; İsviçre; Medeni hukuk; Specific Bequest; Switzerland; Testamentary Disposition; The Legatee; The Obligor of the Legacy; Turkey; Türkiye; Vasiyet; Vasiyet Alacağı; Vasiyet Alacaklısı; Vasiyet Borcu; Vasiyet Borçlusu; Vasiyet Tasarrufu; Vasiyetin Yerine Getirilmesi Legacy; Veraset ve intikal